Effect Of Perceived Usefulness And Perceived Ease Of Use On Intention To Use Mobile Banking (Brimo) With Attitude As Intervening Variable (Study At Lubuk Basung Sub-Branch Office Of Pt. Bank Rakyat Indonesia) - Jordy Arief Fachreza; Eri Besra; Verinita (Enrichment : Journal of Management, 2022)
Abstract The purpose of this study is to examine the effect of perceived usefulness and perceived ease of use on intention to use mobile banking (brimo), using attitude as an intervening variable, at Lubuk Basung Sub-Branch Office of PT. Bank Rakyat Indonesia. Explanatory research was used in this study, with an explanatory survey emphasizing quantitative approaches as the research method. The sample consists of 250 clients of Lubuk Basung Sub-Branch Office of PT. Bank Rakyat Indonesia who use Mobile Banking (BRIMO). Purposive sampling is the sample technique used. Structural Equation Modeling - Partial Least Squares was used to analyze the data (SEM-PLS). The results indicated that perceived usefulness had a significant effect on intention to use, perceived ease of use had a significant effect on intention to use, perceived of usefulness had a significant effect on attitudes of use, attitudes of use had a significant effect on intention to use, and perceived ease of use had a significant effect on intention in use through attitude. This research obtains significant findings for PT. BRI, namely that the banking sector enhances the features offered to customers to make them more comfortable when performing required banking transactions. Additionally, they enhance services through easily accessible mobile applications and personalize the appearance of banking features to meet the customer needs